2023
DOI: 10.3390/biom13020282
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of the TRP Family, Especially TRPV4 and TRPC4, and Its Expression Correlated with Prognosis, Tumor Microenvironment, and Treatment Sensitivity

Abstract: Background: Transient receptor potential (TRP) channels are involved in various physiological, pathological, and tumorigenesis-related processes. However, only a few studies have comprehensively analyzed TRP family members and their association with prognosis and tumor microenvironment (TME) in various cancers. Thus, in this study, we focused on TRP channels in pan-cancer and screened two typical TRP channels, TRPV4 and TRPC4, as examples. Methods: Based on the latest public databases, we evaluated the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Bekele et al specified in their investigation that bladder cancer cell lines are sensible to BRAFV600E inhibitor PLX4720 [54]. Also, Chen et al, determined Transient receptor potential (TRP) family gene expression in bladder and para-carcinoma tissues and TRP expression is associated with the sensibility to several drugs inclusive of PLX-4720 [55]. Otherwise, PLX4720 is applied for other cancer types such as melanoma [56,57] and colorectal carcinoma [58].…”
Section: Discussionmentioning
confidence: 99%
“…Bekele et al specified in their investigation that bladder cancer cell lines are sensible to BRAFV600E inhibitor PLX4720 [54]. Also, Chen et al, determined Transient receptor potential (TRP) family gene expression in bladder and para-carcinoma tissues and TRP expression is associated with the sensibility to several drugs inclusive of PLX-4720 [55]. Otherwise, PLX4720 is applied for other cancer types such as melanoma [56,57] and colorectal carcinoma [58].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research on the mechanisms driving cancer progression has elucidated the pivotal role played by interactions between genes and immune cells within the TME. Chen et al conducted a comprehensive analysis to elucidate the expression patterns of TRP family genes and their association with the tumor microenvironment (TME) across different types of cancer [50]. In a separate study, Feng et al demonstrated a signi cant positive correlation between CENPT and in ltration of myeloid-derived suppressor cells (MDSCs), while a signi cant negative correlation was observed between CENPT and in ltration of T-cell natural killer (NK) cells in the majority of cancer types [51].…”
Section: Discussionmentioning
confidence: 99%
“…To identify variations in the expression of TRAF family genes across different cancers, we utilized RNA sequencing data (FPKM format) along with clinical characteristics, survival information, immune subtypes, and stemness scores (based on DNA methylation and RNA) for 33 cancer types. This data was sourced from TCGA database and accessed via the University of California Santa Cruz (UCSC) Xena data set platform ( http://xena.ucsc.edu/ ) [ 16 ]. Comprehensive details of the 33 cancer types, encompassing abbreviations, full names, the quantity of cancerous and normal samples, and other relevant data, are presented in the Supplementary table (Table S1).…”
Section: Methodsmentioning
confidence: 99%